APPLICATION OF THE METHOD OF CHARACTERISTICS FOR SOLUTION OF THE UNSTEADY NON-ISOTHERMAL NON ADIABATIC FLOW EQUATIONS - Kimambo, C. Z.M. (Tanzania Journal of Engineering and Technology, 2018)
Abstract